2020
DOI: 10.1101/2020.12.18.423280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted cancer therapy induces APOBEC fuelling the evolution of drug resistance

Abstract: Introductory paragraphThe clinical success of targeted cancer therapy is limited by drug resistance that renders cancers lethal in patients1-4. Human tumours can evolve therapy resistance by acquiring de novo genetic alterations and increased heterogeneity via mechanisms that remain incompletely understood1. Here, through parallel analysis of human clinical samples, tumour xenograft and cell line models and murine model systems, we uncover an unanticipated mechanism of therapy-induced adaptation that fuels the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 122 publications
2
13
0
Order By: Relevance
“…Therefore, therapeutic strategies targeting the mechanisms responsible for drug tolerance may prevent, or at least delay, the evolution of acquired resistance (Fig 3 ). This strategy was tested in a recent study where the selective pressure exerted by EGFR inhibitors in lung cancer was shown to induce APOBEC3B overexpression, leading to increased cancer cell mutability, fostering tumour adaptation to treatment (preprint: Mayekar et al , 2020 ). Similar findings were reported in colon cancer, whereby drug‐tolerant cells were shown to temporarily down‐regulate mismatch repair (MMR) and homologous recombination DNA repair genes in favour of error‐prone polymerases as an adaptive response to overcome BRAF and EGFR inhibition (Russo et al , 2019 ).…”
Section: Clinical Opportunities: Leveraging Evolutionary Principlesmentioning
confidence: 99%
“…Therefore, therapeutic strategies targeting the mechanisms responsible for drug tolerance may prevent, or at least delay, the evolution of acquired resistance (Fig 3 ). This strategy was tested in a recent study where the selective pressure exerted by EGFR inhibitors in lung cancer was shown to induce APOBEC3B overexpression, leading to increased cancer cell mutability, fostering tumour adaptation to treatment (preprint: Mayekar et al , 2020 ). Similar findings were reported in colon cancer, whereby drug‐tolerant cells were shown to temporarily down‐regulate mismatch repair (MMR) and homologous recombination DNA repair genes in favour of error‐prone polymerases as an adaptive response to overcome BRAF and EGFR inhibition (Russo et al , 2019 ).…”
Section: Clinical Opportunities: Leveraging Evolutionary Principlesmentioning
confidence: 99%
“…We would therefore hesitate to label genome instability caused by under-expression of replication proteins as a mutagenic response, though our study provides strong support for the suggestion that non-genotoxic drug treatment can increase mutation rate and drive the emergence of resistance. Whether mutagenesis is intentional or not, our study and others addressing drug-induced mutation (28,58) provide grounds for optimism that resistance to targeted chemotherapeutics is preventable, since mutational mechanisms that act during chemotherapy can be characterised and suppressed.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, upregulation of A3B has been observed in many tumors types and has been demonstrated to contribute to the A3 mutational signature [30][31][32]. Moreover, A3B expression in tumor has been shown to fuel genetic diversity of the tumor cells, favoring metastasis and drug resistance [33][34][35]. Finally, one of the limitations of oncolytic viruses' efficacy, is the expression by the host cells of the A3B protein [36].…”
Section: Do Adenoviruses Actively Antagonize A3b By Which Mechanisms?mentioning
confidence: 99%